Ceo material : - Benton, D. A. (McGraw-Hill, 2009)
Sooner or later that plum position is going to become vacant at your workplace. You know you’ll want it, but can you get it? Ask yourself: What’s my track record? Am I smart enough in the right areas? Do people like working with me? Do they respect me? Would they follow me if I were in charge?